2022
DOI: 10.3390/nu14051055
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Zinc, Copper, and Selenium Intakes during Pregnancy and Congenital Heart Defects

Abstract: The effects of zinc, copper, and selenium on human congenital heart defects (CHDs) remain unclear. This study aimed to investigate the associations of the maternal total, dietary, and supplemental intakes of zinc, copper, and selenium during pregnancy with CHDs. A hospital-based case-control study was performed, including 474 cases and 948 controls in Northwest China. Eligible participants waiting for delivery were interviewed to report their diets and characteristics in pregnancy. Mixed logistic regression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Animal studies showed that fetal starvation resulted in congenital heart abnormalities (CHDs) and the infant’s cardiac deformities (Lopez et al 2008 ). CHDs are the most prevalent congenital impairments, with an estimated prevalence of 9.4% of births globally (Liu et al 2019 ); 9% of live births were affected most frequently in China, where more than 150,000 instances are reported yearly (Zhao et al 2019 ; Yang et al 2022 ). In addition, malnourished children are more susceptible to dying from illnesses that commonly affect children, such as measles, malaria, HIV/AIDS, pneumonia, or diarrhea (Black et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Animal studies showed that fetal starvation resulted in congenital heart abnormalities (CHDs) and the infant’s cardiac deformities (Lopez et al 2008 ). CHDs are the most prevalent congenital impairments, with an estimated prevalence of 9.4% of births globally (Liu et al 2019 ); 9% of live births were affected most frequently in China, where more than 150,000 instances are reported yearly (Zhao et al 2019 ; Yang et al 2022 ). In addition, malnourished children are more susceptible to dying from illnesses that commonly affect children, such as measles, malaria, HIV/AIDS, pneumonia, or diarrhea (Black et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cu can pass through the placental barrier through the active transport of two Cu-ATPases (ATP7A and ATP7B), therefore, the fetus may also be affected by maternal Cu status ( 46 ). However, in a recent case–control study conducted by Yang et al, no association was detected between dietary or supplemental Cu intake in mothers during pregnancy and CHDs occurrence in offspring ( 47 ). The results may be interpreted that few pregnant women in the study population had deficient or excessive Cu status.…”
Section: Essential Trace Elements and Congenital Heart Diseasesmentioning
confidence: 93%
“…For instance, higher serum Zn levels were associated with decreased odds of isolated ventricular septum defects (VSDs) in children ( 50 ). A recent study evaluated the association between maternal dietary or supplementary Zn intake during pregnancy and CHDs risks in offspring ( 47 ). The results showed that higher intake of Zn was associated decreased risks of CHDs in offspring.…”
Section: Essential Trace Elements and Congenital Heart Diseasesmentioning
confidence: 99%
“…Tana et al reported that compared with the control group, exercise reduced the prevalence of the DDs in the offspring of GBD mice by 34.5% [80] . Addition to exercise, intaking trace elements is also one of the available approaches to prevent DDs [81][82][83] . This is owing to the pivotal role of trace elements in retaining redox homeostasis and regulating signal transduction pathways and immune function in healthy growth and development of body [84] .…”
Section: Diet Exercisementioning
confidence: 99%